Understanding the public health implications of prisoner reentry in California: phase I report ; prepared for the California Endowment - Davis, Lois M. (Technical report / RAND, 2009)
Socioeconomic and health characteristics of California state prisoners -- Distribution and concentration of parolees in California -- Conceptual framework and methods for defining the health care safety net for parolees -- Counties' capacity to meet the health care needs of the reentry population